The rainbow comes and goes [large type] : a mother and son talk about life, love, and loss - Cooper, Anderson; Vanderbilt, Gloria, 1924-2019- (HarperLuxe, an imprint of HarperCollinsPublishers, 2016)
Correspondence between the CNN journalist and his celebrated mother, exchanged in the aftermath of the latter's brief illness, shares a rare window into their relationship and the life lessons imparted by an aging mother to her adult son.